Mental health literacy: a systematic review of knowledge and beliefs about mental disorders in Malaysia - Munawar, Khadeeja; Mukhtar, Firdaus; Choudhry, Fahad Riaz; Lai, Alvin Oon Ng (John Wiley and Sons Inc, 2021)
Background: Mental health problems in Malaysia are on a rise. This study aimed at performing a systematic review of mental health literacy (MHL) in Malaysia. Methods: Medline, Embase, ERIC/Proquest, ScienceDirect, Pubmed, PsycINFO, CINAHL, Scopus, EBM Reviews - Cochrane Central Register of Controlled Trials, Ovid Emcare and reference lists of included studies were searched in February 2020. Studies that evaluated at least one of the main components of MHL, including (1) knowledge related to mental health issues, and (2) stigma, were included irrespective of study design. As secondary findings, the review also synthesized results related to facilitators and barriers to seeking mental health services. Depending on the research design, the quality of each study was assessed through checklists. Results: Forty six studies published between 1995 to 2019 were included. Most studies used cross-sectional designs to investigate MHL. Findings indicate that most Malaysians have stigmatizing attitudes towards mental health problems. Participants in the included studies endorsed multifactorial explanations of mental health issues with a dominance of supernatural and religious aetiologies. Likewise, the commonest barrier was considering sources other than professional sources of mental-health services. Presence of adequate knowledge and considering providers as competent facilitated help-seeking. Additionally, there was considerable heterogeneity in studies and a lack of standardized measures assessing MHL. Conclusions: There is an increase in studies on MHL in Malaysia. A few of these studies, based on experimental design, have shown positive effects. Researchers, practitioners, and policymakers should develop standardized measures and interventional studies based on all the components of MHL